MODEL ADOPSI SISTEM INFORMASI KESEHATAN (SIK) BERBASIS OPEN SOURCE SOFTWARE (OSS) DI RUMAH SAKIT - , MUHAMAD FAISAL PATAHA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Adoption of health information systems (HIS) is a stage in which the hospital decided to switch from a manual system to a computerized system, which aims to make all hospital activities become more efficient. Strategy adoption of open source software (OSS) in HIS is a potential alternative, especially for health care facilities such as hospitals. OSS adoption is a choice made by the hospitals to budget savings and ease of development of HIS. Adoption of OSS have support the Indonesian government's program \"Indonesia Goes Open Source\" (IGOS), in addition to this study because of the hospitals are adopting of HIS based on OSS especially in Indonesia has become the primary choice that hospitals requires a lot of literature that are useful in the decision making process in the adoption of HIS based on OSS in hospitals. Objective : To identify characteristics of hospitals, identifying the characteristics of OSS, and describe the strategy for adoption OSS in hospitals. Methods : This study used a qualitative method, case study design, and using a type of holistic multi-case is one problem with a lot of places. The process of data collection using the instrument of observation and interviews live \"face to face\". The subjects for in this study were managers, staff and programmers are there exist in the unit of information technology (IT) in the hospital. Results : The findings in this study indicate that hospitals par adoption the HIS based on OSS much going on Electronic Medical Records, Hospital Information Systems, Pharmacy Information Systems, and Laboratory Information Systems. Moreover, in minimizing the rejection rate of Human Resources at hospitals to implementation of new technologies, namely the nonformal approach. The cost factor is not a major factor in the hospital for IT managers when deciding to use OSS in HIS. The role of OSS vendors are quite different, namely to transfer their knowledge of information systems used in hospitals, and also the support of the University of significantly influence hospital decisions in the adoption of HIS based on OSS in the hospital .